Avidity of thyroglobulin antibody in sera from patients with Hashimoto's thyroiditis with different thyroid functional status - Zhang, Y (Blackwell Science Inc, 2010)
The mechanism of disease progression in Hashimoto's thyroiditis (HT) is still unclear. Thyroglobulin antibody (TgAb) is a diagnostic hallmark of HT. The aim of our study was to evaluate the avidity of TgAb in sera from HT patients with different thyroid functional status. Sera from 50 patients with newly diagnosed HT were collected and divided into three groups according to thyroid function: patients with hypothyroidism (H, n = 18), subclinical hypothyroidism (sH, n = 18) and euthyroidism (Eu, n = 14). Titres and avidity of TgAb were determined by enzyme-linked immunosorbent assays (ELISAs). Avidity constant (aK) was determined as the reciprocal value of the thyroglobulin molar concentration in the liquid phase resulting in 50% inhibition of TgAb binding to thyroglobulin in solid-phase ELISAs. The titres and aK of TgAb were performed using log-transformation, and expressed as lgT and lgaK, respectively. Mean lgT of TgAb in sera was 4·19 ± 0·60 in H, 3·77 ± 0·63 in sH, and 3·29 ± 0·64 in Eu, respectively. The median avidity of TgAb was 2·30 × 10(9) in H, 8·80 × 10(8) in sH, 2·00 × 10(7) in Eu, respectively. lgT and lgaK of TgAb were at significantly lower levels in Eu than in sH and H (P < 0·05). Correlation was found between lgT and lgaK (r = 0·594, P < 0·05). lgaK was also related to TSH (r = 0·308, P < 0·05). Our study indicated that patients with high-avidity TgAb might be at high risk of developing subclinical, even to overt, hypothyroidism.